BATIK MALUKU: EKSPLORASI KEKAYAAN REMPAH-REMPAH MELALUI BATIK MALUKU - Shopia Himatul Alya; Sari Dewi Kuncoroputri; Ariesa Pandanwangi (Jurnal Bahasa Rupa, 2022)
Maluku is famous as a spice-producing archipelago. Spices are not the only richness that Maluku has.. Maluku also has other cultural richness that are no less unique, namely Maluku Batik. The cultural richness and natural wealth of Maluku have inspired local people to apply the visual beauty of spices to batik motifs and ornaments which later became the hallmark of Maluku Batik. This research aims to analyze the visual application of spices in Maluku batik cloth. The sample included in this study were the batik cloths made by Malukubatik artists. The method that is employed in this research is a qualitative descriptive method by studying decorative styles inspired by the typical spices of Maluku batik. The results of this research study show that Maluku batik is very representative of the local wisdom of its people. Other findings from this study indicate that in general, batik motifs can be sorted based on their historical and cultural backgrounds. The glory of Maluku as a trade route for herbs and spices has been embedded in the collective memory of the Maluku people. One of these collective memories is immortalized through Maluku batik.